A viral movement protein mediates host volatile biosynthesis to co-attract vectors and non-vectors and enhances viral infection - Li, Shijun; Luo, Xiangwen; Zhang, Yu; Zhang, Zhanhong; Yang, Xiao; Zhou, Xuguo; Wang, Xin; OuYang, Xian; Qu, Xiaoxin; Zhang, Deyong; Zhang, Songbai; Liu, Yong (Frontiers in Plant Science, 2025)
The literature shows that vector-transmitted plant viruses mediate host volatile biosynthesis to attract vectors and repel non-vectors, benefiting plant-infecting viruses and enhancing their spread. In this study, pepper veinal yellows virus (PeVYV) and its encoded movement protein P4 were shown to mediate host volatile biosynthesis to co-attract its exclusive vector aphids and non-vector Q-whiteflies; both have been proven to have existing food competition. The P4 protein enhances the biosynthesis of three volatiles and reduces the biosynthesis of one volatile involved in co-attracting and co-repelling aphids and Q-whiteflies. Viral replication is enhanced significantly in plants co-fed on by aphids and Q-whiteflies compared with plants fed on individual insects. Viral replication is enhanced significantly in the early stage for plants fed on by Q-whiteflies while in the late stage for plants fed on by aphids. Trans-zeatin (tZ) biosynthesis was increased in plants fed on by aphids and Q-whiteflies, and tZ enhanced viral replication in these plants. These data suggest that the PeVYV P4 protein mediates host volatile biosynthesis to co-attract vectors and non-vectors, benefiting viral infection probably by enhancing tZ biosynthesis. Data in this study have broad implications regarding the ecological significance of whiteflies in various agricultural ecosystems where aphids are the key viral transmitters.